Socio-Cultural Values in The Film: Semiotic Study of Charles Sanders Peirce on Farha - Ridho, Mohammad Rosyid; Aulia Safitri; Zalifa Nuri (Lughaat: Journal of Arabic Linguistics, 2025)
This paper analyzes the social and cultural values represented in the film Farha using Charles Sanders Peirce's semiotic approach. The film Farha portrays the life of Palestinian society before and during colonization through the perspective of a young girl struggling to survive in a world fraught with division and conflict. By focusing on her journey, the film provides a poignant depiction of the challenges, aspirations, and transformations within Palestinian society. As a work of visual storytelling, Farha serves as a medium to shed light on the historical and social realities faced by Palestinians. This paper aims to explore the socio-cultural values embedded in the film, particularly in relation to traditional customs, educational aspirations, and shifting gender roles. The study employs Peirce's triadic semiotic model, which consists of three key elements: the representamen (the sign itself), the object (what the sign refers to), and the interpretant (the meaning derived by the audience). Through this approach, the research seeks to uncover the deeper significance behind the film's symbolic elements and their implications for understanding Palestinian cultural identity. The findings of this study indicate that Farha depicts Palestinian society as one that is deeply rooted in traditional social values, emphasizing community, resilience, and familial bonds. Furthermore, the film brings attention to the importance of education as a means of empowerment, particularly for women. The protagonist's aspiration for education symbolizes a broader societal shift toward gender equality and self-determination, highlighting the evolving roles of women in Palestinian society.